Preparation method and application of manganese-containing bioglass composite membrane material

By introducing manganese-doped bioglass into the PLGA/PCL composite membrane, a composite membrane with excellent barrier function and anti-inflammatory properties was prepared, which solved the limitations of the existing guided bone regeneration membrane in bone regeneration and anti-inflammatory, and achieved significant bone regeneration effect in alveolar bone defect repair.

CN119587772APending Publication Date: 2025-03-11NANJING STOMATOLOGICAL HOSPITAL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807572.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing guided bone regeneration membranes have limitations in promoting osteogenesis, anti-inflammatory, angiogenesis and bone tissue repair, especially in areas with severe bone defects, which are not ideal for bone regeneration.

Method used

Manganese-doped bioglass (Mn-MBG) was introduced into the PLGA/PCL composite membrane, and composite membrane materials were prepared by electrospinning method, combining the antioxidant function of manganese ions and the osteoinductive ability of bioglass to improve the mechanical properties, degradation properties and anti-inflammatory properties of the membrane.

Benefits of technology

The excellent effect of composite membrane in alveolar bone defect repair is achieved, which significantly promotes angiogenesis and bone tissue repair, effectively prevents postoperative infection, and achieves ideal bone regeneration in areas with severe bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587772A_ABST
    Figure CN119587772A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a manganese-containing bioglass composite membrane material, and belongs to the technical field of biomedical materials. The method for preparing the manganese-containing bioglass composite membrane material comprises the following steps: slowly adding a solution 1 into a solution 2, and stirring; adding TEP and stirring, adding calcium nitrate tetrahydrate and manganese nitrate tetrahydrate, and stirring to obtain a Mn-MBG spray precursor solution; carrying out spray drying and calcination on the Mn-MBG spray precursor solution; and adding hexafluoroisopropanol into the mixture, stirring to obtain an electrostatic spinning precursor solution, and carrying out electrostatic spinning. The composite membrane has the advantages of good anti-oxidative stress and anti-inflammatory effects, effective removal of ROS (reactive oxygen species), adjustment of M1 / M2 polarization of macrophages and the like. In addition, the composite membrane also has excellent mechanical properties, continuous ion release ability and remarkable biological activity, promotes functions of osteoblasts and vascular endothelial cells and regulates immune response, and can be applied to the field of bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a preparation method and application of a manganese-containing bioglass composite membrane material. Background Art

[0002] Alveolar bone defect is a common oral disease. Alveolar bone defect of varying degrees caused by trauma, tumors, periodontitis and long-term tooth loss has become a huge challenge for subsequent implant restoration, orthodontic and periodontal treatment. Methods to improve alveolar bone defects include guided bone regeneration (GBR), bone compression, maxillary sinus lift, distraction osteogenesis and autologous large bone transplantation. GBR is considered to be one of the most commonly used surgical methods for reconstructing alveolar bone to treat alveolar bone defects. As shown in the GBR principle, the barrier membrane principle is used to block the rapidly proliferating epithelium and connective tissue outside the membrane and promote the growth of osteoblasts that grow slowly and can form bone inside the membrane. At present, it is recommended to use GBR technology to increase alveolar bone before / during dental implantation and before / during orthodontic treatment. It has become a widely recognized method for repairing alveolar bone defects. Guided bone regeneration usually requires the implantation of a barrier membrane to maintain bone regeneration space while implanting autologous bone or other bone filling materials. Therefore, the barrier membrane used for GBR is a necessary and basic material to maintain the bone regeneration process.

[0003] At present, many studies have been conducted to develop ideal GBR membrane materials, which include various natural and synthetic materials. A large number of clinical studies have demonstrated their clinical effects, however, these GBR membranes still have limitations in promoting osteogenesis and anti-inflammatory properties. Therefore, more and more modification methods and materials have been developed in recent years, providing new approaches for the development of GBR therapy. These modification methods and materials include the use of nanotechnology to improve the physical and chemical properties of the membrane, the direct integration of bioactive factors or drugs into the GBR membrane to promote bone regeneration, or enhance its anti-inflammatory ability. These developments not only enhance the functionality of the GBR membrane, but also improve its clinical application potential in periodontal and maxillofacial bone defect reconstruction.

[0004] Incorporating bioactive ingredients into barrier membranes or modifying their structures is the main method to enhance osteogenic performance. Various inorganic materials are added to GBR membranes to induce the growth of osteoblasts and promote bone tissue proliferation. Hydroxyapatite (HA), β-tricalcium phosphate (β-TCP) and bioactive glass (BG) are the most commonly studied inorganic materials. BG is the most bioactive type of bioceramic material with biphasic functions of osteoconduction and osteoinduction. It can release calcium and silicate ions, enhance the activity of osteoblasts, and stimulate bone formation and angiogenesis. BG alone has no antioxidant function and cannot remove ROS and oxidative stress, which to a certain extent limits its application in inflammatory environments.

[0005] In addition, at present, achieving effective regeneration of periodontal bone tissue still faces challenges. An ideal guided bone regeneration membrane should have good biocompatibility, excellent barrier function, a degradation rate that matches the bone formation rate, appropriate mechanical strength, excellent anti-inflammatory properties, and excellent osteoinduction and osteoconduction capabilities. However, even though commercialized guided bone regeneration membranes, especially absorbable membranes, have been widely used clinically, their rapid degradation, insufficient mechanical properties, poor anti-inflammatory effects, limited osteogenesis and angiogenesis, as well as poor postoperative infection prevention effects and difficulty in achieving ideal bone regeneration in severe bone defect areas still need to be addressed.

[0006] Manganese (Mn) is one of the essential trace elements for the human body, and Mn oxide nanomaterials have good antioxidant properties. 2 Nanozyme shells have inherent SOD-like and CAT-like activities that can protect cells from toxic chemicals (such as H 2 O 2 ) and other oxidative damage, significantly reducing the level of intracellular ROS under oxidative stress and reducing oxidative damage to cells. In addition, Mn ions also enhance osteogenic properties in a dose-dependent manner. The osteoconduction and osteoinduction properties of PLGA / PCL membranes are weak, so it is necessary to add bioactive molecules to the PLGA / PCL electrospun fiber membrane or modify the surface to enhance its biological activity. Therefore, if BG and Mn ions are introduced into the PLGA / PCL composite membrane at the same time, it is expected to obtain a guided bone tissue regeneration membrane with superior mechanical properties, degradation properties, anti-inflammatory and osteogenesis. Summary of the invention

[0007] The purpose of the present invention is to provide a preparation method and application of a manganese-containing bioglass composite membrane material to overcome the shortcomings of the above-mentioned prior art. The composite membrane has excellent barrier function and anti-inflammatory properties, can promote angiogenesis and bone tissue repair, effectively prevent postoperative infection, and achieve ideal bone regeneration effects in severe bone defect areas.

[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a manganese-containing bioglass composite membrane material, wherein the steps for preparing the manganese-containing bioglass composite membrane material are as follows:

[0009] S1: preparing solution 1: adding polyether to deionized water and stirring for 2 h and adjusting the pH by adding nitric acid when the solution is transparent and clear to obtain solution 1;

[0010] S2: Preparation of solution 2: TEOS was added to a nitric acid solution at pH = 1 and stirred vigorously until clear to obtain solution 2;

[0011] S3: preparing a Mn-MBG spray precursor solution: slowly adding the solution 1 to the solution 2, and continuing to stir for 1 hour; adding TEP and stirring for 1 hour, and then adding calcium nitrate tetrahydrate and manganese nitrate tetrahydrate, and stirring for 1 hour to obtain a Mn-MBG spray precursor solution;

[0012] S4: preparing Mn-MBG powder: spray drying and calcining the Mn-MBG spray precursor solution;

[0013] S5: Preparation of PLGA / PCL / Mn-MBG bioglass composite membrane material: Weigh PLGA, PCL, and Mn-MBG, add hexafluoroisopropanol to the mixture of the PLGA, the PCL, and the Mn-MBG, stir for 24 hours to obtain an electrospinning precursor solution, and perform electrospinning.

[0014] Preferably, in S1, the pH of solution 1 is 1-2; the polyether is P123, with a molecular weight of 5800 and a mass fraction of 32.0; the mass fraction of deionized water is 330; in S2, the mass fraction of TEOS is 107.2, and the mass fraction of nitric acid solution is 56; in S3, the mass fraction of TEP is 11.7, the mass fraction of calcium nitrate tetrahydrate is 19.7, and the mass fraction of manganese nitrate tetrahydrate is 3.2; in S5, the mass fraction of PLGA is 0.7, the mass fraction of PCL is 0.3, the mass fraction of Mn-MBG is 0.5, and the mass fraction of hexafluoroisopropanol is 7.5.

[0015] Preferably, in S4, the spray drying specific airflow mode setting parameters are as follows: atomization pressure 0.4 MPa; feed rate 72 ml / min; inlet temperature 250°C.

[0016] Preferably, in S4, the calcination parameters are set as follows: heating to 800°C at 2°C / min and keeping the temperature for 3h, cooling with the furnace, and finally obtaining Mn-MBG powder.

[0017] Preferably, in said S5, the specific preparation is as follows:

[0018] The electrospinning precursor solution was loaded into a 20 mL syringe, and a 20G needle was used for electrospinning. The parameters were set as follows: receiving distance 13 cm, spinning voltage 15.5 kV, feed rate 1 mL / h, drum speed 300 rpm, and finally a bioglass composite film was obtained.

[0019] The invention discloses an application of a manganese-containing bioglass composite membrane material obtained by a method for preparing a manganese-containing bioglass composite membrane material in repairing bone defects.

[0020] A method for preparing a manganese-containing bioglass composite membrane material and application of the manganese-containing bioglass composite membrane material in repairing alveolar bone defects.

[0021] The invention discloses an application of a manganese-containing bioglass composite membrane material obtained by a method for preparing the manganese-containing bioglass composite membrane material in repairing skull defects.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention has a wide range of applications, excellent performance in anti-oxidative stress and anti-inflammatory aspects, can effectively remove ROS and regulate the M1 / M2 polarization of macrophages. The PLGA / PCL / Mn-MBG composite membrane promotes the functions of osteoblasts and vascular endothelial cells, and regulates immune responses due to its excellent mechanical properties, sustained ion release ability and significant biological activity. The composite membrane is used in the field of repairing bone defects, especially in clinical dental applications, showing great potential for repairing alveolar bone defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a photograph of the appearance of the PLGA / PCL electrospun membrane prepared in Example 1;

[0025] Figure 2 is a photograph of the appearance of the PLGA / PCL / Mn-MBG composite membrane prepared in Example 1;

[0026] Figure 3 The SEM images of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1;

[0027] Figure 4 It is the particle size distribution diagram of Mn-MBG microsphere material;

[0028] Figure 5 The degradation rate and ion release measurement results of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 are shown in FIG.

[0029] Figure 6 H of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1 2 O 2 Clear the curve;

[0030] Figure 7 Micro-CT evaluation of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1 for repairing alveolar bone defects caused by periodontitis;

[0031] Figure 8 Micro-CT evaluation of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 for repairing skull defects in SD rats;

[0032] Fig. 9 Immunohistochemistry of blood vessel-related proteins in the repair of SD rat skull defects by the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1;

[0033] Fig.10 The effects of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1 on the M1 / M2 polarization of RAW264.7;

[0034] Fig.11 Immunohistochemical staining of macrophage polarization-related proteins of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 when repairing alveolar bone defects caused by periodontitis;

[0035] Fig.12 Immunofluorescence staining of macrophage polarization-related proteins of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 when repairing alveolar bone defects caused by periodontitis;

[0036] Fig.13 The effect of bioglass composite membrane on HUVECs proliferation under inflammatory environment;

[0037] Fig.14 The effects of electrospun membranes and bioglass composite membranes on HUVECs migration under different environments;

[0038] Fig.15 The effect of electrospun membrane and bioglass composite membrane on the expression of CD31 in HUVECs cells;

[0039] Fig.16 The effects of electrospun membrane and bioglass composite membrane on VEGF protein expression in HUVECs cells;

[0040] Fig.17 The effect of bioglass composite membrane on the expression of HUVECs angiogenic differentiation-related genes Vegf and Kdr under normal / inflammatory environment;

[0041] Fig.18 This is the appearance diagram of the flexibility of the PLGA / PCL / Mn-MBG composite membrane;

[0042] Fig.19 The tensile strength and tensile strain diagram of PLGA / PCL / Mn-MBG composite membrane. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0044] Example 1

[0045] MBG was synthesized by spray drying: 32.0 g of polyether (P123) was added to 330 g of deionized water and stirred for 2 h. When the solution was transparent and clear, nitric acid was added to adjust the pH to 1-2 to obtain solution 1. 107.2 g of TEOS was added to 56 g of nitric acid solution with pH = 1 and stirred vigorously until it was clear (about 30 min) to obtain solution 2. Solution 1 was slowly added to solution 2 and continued to stir for 1 h. Then 11.7 g of TEP was added and stirred for 1 h, and finally 22.8 g of calcium nitrate tetrahydrate was added and stirred for 1 h to obtain the MBG spray precursor solution. After that, spray drying and calcination were performed. MBG microspheres were prepared by spray drying the precursor solution using a spray dryer (airflow mode). The specific airflow mode setting parameters are as follows: atomization pressure 0.4 MPa, feed rate 72 ml / min, inlet temperature 250 ° C. The MBG microspheres obtained by spraying were placed in a muffle furnace, and the calcination parameters were set as follows: starting from room temperature, the temperature was increased to 800°C at 2°C / min and kept at this temperature for 3h, and then cooled with the furnace to finally obtain MBG powder.

[0046] Synthesis of Mn-MBG: The initial synthesis steps were the same as MBG. After adding 11.7 g of TEP and stirring for 1 h, 19.7 g of calcium nitrate tetrahydrate and 3.2 g of manganese nitrate tetrahydrate were added and stirred for 1 h to obtain the Mn-MBG spray precursor solution. The spray drying and calcination parameter patterns were the same as before, and Mn-MBG powder was finally obtained.

[0047] Bioglass composite membranes with different compositions were prepared by electrospinning. The electrospinning precursor solution formula is as follows: PLGA: 1.0g PLGA; PLGA / PCL: 0.7g PLGA+0.3g PCL; PLGA / PCL / MBG: 0.7g PLGA+0.3g PCL+0.5g MBG; PLGA / PCL / Mn-MBG: 0.7g PLGA+0.3g PCL+0.5g Mn-MBG. 7.5g hexafluoroisopropanol was added to the above four mixtures respectively, and the electrospinning precursor solution was obtained by stirring for 24h, which was loaded into a 20mL syringe and electrospun using a 20G needle. The parameters were set as follows: receiving distance 13cm, spinning voltage 15.5kV, feeding speed 1mL / h, drum speed 300rpm, and finally the corresponding bioglass composite membrane was obtained.

[0048] Among them, TEOS is tetraethyl silicate; TEP is triethyl phosphate; PLGA is poly(lactide-glycolide) and PCL is poly(caprolactone); MBG is mesoporous bioactive glass; and Mn-MBG is manganese-doped mesoporous bioactive glass.

[0049] Composite film effect test:

[0050] (1) Morphology-SEM image

[0051] Figure 3 The SEM images of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1. The SEM images of the PLGA / PCL electrospun membrane (left), PLGA / PCL / MBG (middle) and PLGA / PCL / Mn-MBG (right) composite membrane prepared in Example 1. The SEM images show that the PLGA / PCL electrospun membrane has a typical polymer electrospun membrane structure, and the MBG and Mn-MBG microspheres are physically embedded and adhered to the surface of the PLGA / PCL fibers. The particle size of the MBG microspheres is less than 35 μm, and is mainly concentrated in the range of 6-14 μm. Figure 4 It is the particle size distribution diagram of Mn-MBG microsphere material. Mn-MBG microspheres are physically embedded and adhered to the surface of PLGA / PCL fibers. The surface of Mn-MBG microspheres is wrapped by PLGA / PCL polymer fibers, which may reduce its degradation rate but increase its mineralization ability at the same time.

[0052] PLGA / PCL polymer fibers are not affected by the particle size of Mn-MBG materials.

[0053] (2) Degradation rate and ion release measurement

[0054] Figure 5 The degradation rate and ion release measurement results of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 are shown in Figure 1. In the figure, A: represents the degradation rate curve; B: represents the ion release curve of PLGA / PCL / MBG; C: represents the ion release curve of PLGA / PCL / Mn-MBG composite membrane. The degradation rate and ion release experiments of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 include the following steps:

[0055] ①, PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane were immersed in Tris-HCl solution, and their degradation rates were detected by measuring the weight at different time points. The degradation rate experiment showed that the degradation rate of PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes after 8 weeks (about 35%) was much higher than that of PLGA / PCL electrospun membrane (10%).

[0056] ②, the ion release capacity of each group was compared by detecting the ion concentration in the solution, and the concentration of Ca, Si, and Mn ions in the solution at different time points was determined by inductively coupled plasma atomic emission spectrometry. MBG in both PLGA / PCL / MBG and PLGA / PCL / Mn-MBG (Figure C) composite membranes can release active ions Ca, Si, and Mn, and the ion release capacity of Mn-MBG is stronger than that of MBG (Figure B).

[0057] (3)H 2 O 2 Clear Test

[0058] Figure 6 H of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1 2 O 2 Clearance curves. H of PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1 2 O 2 The clearance experiment showed that the PLGA / PCL / Mn-MBG composite membrane had good H clearance performance. 2 O 2 Ability to significantly reduce the production of reactive oxygen species in cells.

[0059] (4) Micro-CT evaluation of repairing alveolar bone defects caused by periodontitis

[0060] Figure 7 Micro-CT evaluation of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 in repairing alveolar bone defects caused by periodontitis. Micro-CT evaluation of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 in repairing alveolar bone defects caused by periodontitis.

[0061] Using Micro-CT to reconstruct alveolar bone, no obvious alveolar bone resorption was observed in the Control group, while significant bone resorption and root surface exposure occurred in the Peridontitis group. Compared with the Control group, the number and thickness of trabeculae (Tb.N and Tb.Th) decreased. Compared with the Peridontitis and PLGA / PCL electrospun membrane treatment groups, the PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups showed a significant reduction in alveolar bone loss, a significant increase in the number and thickness of trabeculae (Tb.N and Tb.Th), and a more continuous and orderly arrangement of trabeculae.

[0062] The results of quantitative analysis of new bone showed that compared with the peridontitis and PLGA / PCL electrospun membrane treatment groups, the BV / TV, BS / TV (ratio of bone surface area to tissue volume) and BMD (bone density) statistical values ​​of the PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups increased, which was statistically significant. There was no difference in the BV / TV and BS / TV ratios between the PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups. Compared with the PLGA / PCL / MBG composite membrane treatment group, the BMD, Tb.Th (trabecular thickness) and Tb.N (trabecular number) statistical values ​​of the PLGA / PCL / Mn-MBG composite membrane treatment group increased, which was statistically significant. The above results show that the PLGA / PCL / Mn-MBG composite membrane has a significant bone regeneration effect in the treatment of alveolar bone defects caused by periodontitis.

[0063] (5) Micro-CT evaluation of repair of skull defects in SD rats

[0064] Figure 8 Micro-CT evaluation of the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 in repairing SD rat skull defects.

[0065] The results showed that: Micro-CT results showed that there was no obvious new radiopaque image at the bottom and edge of the skull defect, indicating that there was no obvious bone regeneration in the Control group. In the PLGA / PCL electrospun membrane treatment group, a small amount of irregular bone was formed at the bottom of the skull defect, and a small amount of irregular new bone was seen at the edge of the defect. The cavity of the skull defect was slightly reduced, but most of the defect area was not repaired. A thicker layer of new bone tissue was formed in the skull defect area in the PLGA / PCL / MBG composite membrane treatment group and the PLGA / PCL / Mn-MBG composite membrane treatment group, and the defect area was reduced. There was no difference between the PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups, but it was significantly more than the PLGA / PCL electrospun membrane group. The PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups showed significant effects in increasing bone mass at the bone defect site, improving BV / TV and BS / TV, increasing bone mineral density, and increasing the number and thickness of trabeculae.

[0066] In the composite membrane repair animal model of skull and alveolar bone defects, Micro-CT analysis showed that the formation of new bone in the PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups was significantly higher than that in the control group and PLGA / PCL electrospun membrane treatment group compared with the other two groups.

[0067] (6) Immunohistochemical detection of vascular-related proteins in repairing skull defects in SD rats

[0068] Fig. 9 Immunohistochemistry of blood vessel-related proteins in the repair of SD rat skull defects by the PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membranes prepared in Example 1. Immunohistochemistry staining showed that the expression of VEGF (Figure A) and CD31 (Figure B) proteins was significantly increased. Immunohistochemistry was used to detect the expression of angiogenesis-related factors in each treatment group. The results showed that compared with the Control group, the PLGA / PCL electrospun membrane treatment group and the PLGA / PCL / MBG composite membrane treatment group, the angiogenesis-related factors VEGF and CD31 in the PLGA / PCL / Mn-MBG composite membrane treatment group had more and stronger yellow-stained positive particles, more obvious expression, and the difference was statistically significant.

[0069] (7) Impact on RAW264.7 M1 / M2 polarization

[0070] Fig.10 The effect of PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 on M1 / M2 polarization of RAW264.7. The PLGA / PCL electrospun membrane, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane prepared in Example 1 had an effect on M1 / M2 polarization of RAW264.7. Flow cytometry showed that the extract of PLGA / PCL / Mn-MBG composite membrane could significantly reduce the proportion of M1 and increase the proportion of M2.

[0071] from Fig.10 and Fig.11The results showed that compared with the Periodontitis group, the M1 macrophages in the periodontal tissues of the PLGA / PCL, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups decreased to varying degrees, but only the PLGA / PCL / Mn-MBG composite membrane treatment group had statistical significance, and the proportion of iNOS positive cells was lower than that of the other two treatment groups. Compared with the Periodontitis group, the M2 macrophages in the periodontal tissues of the PLGA / PCL, PLGA / PCL / MBG and PLGA / PCL / Mn-MBG composite membrane treatment groups increased to varying degrees, but only the PLGA / PCL / Mn-MBG composite membrane treatment group had statistical significance, and the proportion of Arg1 positive cells was higher than that of the other two treatment groups.

[0072] F4 / 80, also known as the growth factor-like motif-containing mucin-like hormone receptor, is a marker for mature macrophages. F4 / 80 was double-stained with iNOS (M1 macrophages) and Arg1 (M2 macrophages) by immunofluorescence staining to observe co-localization. Fig.12 As can be seen, the staining results were consistent with the histochemistry. In the PLGA / PCL / Mn-MBG composite membrane treatment group, the number of F4 / 80+ / Arg1+ double-positive M2 macrophages increased, and the number of F4 / 80+ / iNOS+ double-positive M1 macrophages decreased.

[0073] (8) Effect of bioglass composite membrane on HUVECs proliferation under inflammatory environment

[0074] from Fig.13 It was concluded that under inflammatory conditions, cell proliferation increased significantly in the PLGA / PCL / Mn-MBG composite membrane group on days 1, 3, and 5. Under inflammatory conditions, HUVECs proliferation was significantly increased in the PLGA / PCL / MBG composite membrane group compared with the Control group on days 1 and 3.

[0075] (9) Effects of bioglass composite membrane on HUVECs migration under normal / inflammatory conditions

[0076] Fig.14 In the figure, (A) the effect of membrane extract on HUVECs migration under normal / (B) inflammatory conditions and (C) quantitative analysis. Fig.14 It was concluded that PLGA / PCL / Mn-MBG and PLGA / PCL / MBG composite membranes can significantly promote HUVECs cell migration. Under inflammatory conditions, cell migration in all materials was inhibited, but PLGA / PCL / Mn-MBG composite membranes can reduce the adverse effects of inflammatory environment on cell migration, and HUVECs cell migration increased compared to other groups.

[0077] (10) Effects of bioglass composite membrane on CD31 and VEGF protein expression under normal / inflammatory conditions

[0078] Fig.15 (A) Fluorescence microscopic manifestation (A, B) and (C) quantitative analysis of the effects of different membrane extracts on the expression of CD31, angiogenesis-related protein in HUVECs under (A) normal / (B) inflammatory environment. Fig.16 Figure 3. (A) Fluorescence microscopic expression of the effects of different membrane extracts on the expression of VEGF, angiogenesis-related protein in HUVECs, under (A) normal / (B) inflammatory conditions and (C) quantitative analysis. Under normal / inflammatory conditions, PLGA / PCL / Mn-MBG composite membranes can significantly promote CD31 expression. The expression of CD31 protein in PLGA / PCL / MBG composite membranes is also significantly increased compared with PLGA / PCL electrospun membranes and Control. VEGF immunofluorescence staining and mean fluorescence intensity statistical results show that its expression trend is similar to that of CD31.

[0079] (11) Effects of bioglass composite membrane on the expression of HUVECs angiogenic differentiation-related genes Vegf and Kdr under normal / inflammatory conditions

[0080] from Fig.17 It can be seen that in the normal environment (group A) and inflammatory environment (group B), the expression of Vegf and Kdr genes in the PLGA / PCL / Mn-MBG composite membrane was significantly increased compared with other groups. Compared with the PLGA / PCL electrospun membrane and the Control group, the expression of Vegf and Kdr genes in the PLGA / PCL / MBG composite membrane was also significantly increased.

[0081] (12) Mechanical properties of PLGA / PCL / Mn-MBG composite membranes

[0082] from Fig.18 It can be seen that the synthesized PLGA / PCL / Mn-MBG composite membrane is cuttable, foldable, bendable and stretchable, which is conducive to making corresponding adjustments according to the alveolar bone defect area in clinical practice and is convenient for clinical use.

[0083] from Fig.19 It can be seen that through mechanical tests, the tensile strength and tensile strain of the composite membrane doped with MBG or Mn-MBG are greatly reduced. With the increase of Mn-MBG content, the tensile strength and tensile strain of the composite membrane decrease accordingly, and the mechanical properties of the composite membrane change from the typical flexibility of polymers to the typical brittleness of inorganic materials.

[0084] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a manganese-containing bioglass composite film material, characterized in that: The preparation steps of the manganese-containing bioglass composite membrane material are as follows: S1: preparing solution 1: adding polyether to deionized water and stirring for 2 h and adjusting the pH by adding nitric acid when the solution is transparent and clear to obtain solution 1; S2: Preparation of solution 2: TEOS was added to a nitric acid solution at pH = 1 and stirred vigorously until clear to obtain solution 2; S3: preparing a Mn-MBG spray precursor solution: slowly adding the solution 1 to the solution 2, and continuing to stir for 1 hour; adding TEP and stirring for 1 hour, and then adding calcium nitrate tetrahydrate and manganese nitrate tetrahydrate, and stirring for 1 hour to obtain a Mn-MBG spray precursor solution; S4: preparing Mn-MBG powder: spray drying and calcining the Mn-MBG spray precursor solution; S5: Preparation of PLGA / PCL / Mn-MBG bioglass composite membrane material: Weigh PLGA, PCL, and Mn-MBG, add hexafluoroisopropanol to the mixture of the PLGA, the PCL, and the Mn-MBG, stir for 24 hours to obtain an electrospinning precursor solution, and perform electrospinning.

2. The method for preparing a manganese-containing bioglass composite film material according to claim 1, characterized in that: In the S1, the pH of the solution 1 is 1-2; the polyether is P123, with a molecular weight of 5800 and a mass fraction of 32.0; the mass fraction of the deionized water is 330; in the S2, the mass fraction of TEOS is 107.2, and the mass fraction of the nitric acid solution is 56; in the S3, the mass fraction of TEP is 11.7, the mass fraction of calcium nitrate tetrahydrate is 19.7, and the mass fraction of manganese nitrate tetrahydrate is 3.2; in the S5, the mass fraction of PLGA is 0.7, the mass fraction of PCL is 0.3, the mass fraction of Mn-MBG is 0.5, and the mass fraction of hexafluoroisopropanol is 7.

5.

3. The method for preparing a manganese-containing bioglass composite membrane material according to claim 1, characterized in that: In S4, the specific airflow mode setting parameters of the spray drying are as follows: atomization pressure 0.4 MPa; feed rate 72 ml / min; inlet temperature 250°C.

4. The method for preparing a manganese-containing bioglass composite membrane material according to claim 1, characterized in that: In S4, the calcination parameters are set as follows: heating to 800°C at 2°C / min and keeping the temperature for 3h, cooling with the furnace, and finally obtaining Mn-MBG powder.

5. The preparation method and application of a manganese-containing bioglass composite membrane material according to claim 1, characterized in that: In the S5, the specific preparation is as follows: The electrospinning precursor solution was loaded into a 20 mL syringe, and a 20G needle was used for electrospinning. The parameters were set as follows: receiving distance 13 cm, spinning voltage 15.5 kV, feed rate 1 mL / h, drum speed 300 rpm, and finally a bioglass composite film was obtained.

6. Use of a manganese-containing bioglass composite membrane material obtained by the method for preparing a manganese-containing bioglass composite membrane material according to any one of claims 1 to 5 in repairing bone defects.

Citation Information

Cited By

  • Wound repair material based on PRF and preparation method thereof

    CN120884733A